Podobni spovedi s Krasa in iz Provanse - Matičetov, Milko (Traditiones (Ljubljana), 1999)
In this article the author anlyzes the motif of confession in a poem entitled "Mirelo", connecting it with an event from his own youth. The poem probably orginating from folk tradition, was written by Mistral, a poet from provence
Keywords: ljudsko slovstvo; oral literature; slovstvena folklora; Slovene literature; slovenska književnost; karst; Kras